ULTIMUM REMEDIUM AS A MECHANISM FOR STATE LOSS RECOVERY IN CORPORATE TAX CRIMES: AN ISLAMIC LAW PERSPECTIVE - Hakim, Nur; Yuhelson, Yuhelson (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The principle of ultimum remedium in tax criminal law is designed as thefinal boundary of law enforcement, to be used only when administrativemeasures are no longer effective. However, in the practice of handlingcorporate tax crimes in Indonesia, this principle is often disregarded,resulting in punishment becoming the first step rather than the last resort.This study aims to analyze the effectiveness of ultimum remedium as amechanism for state loss recovery and to assess the extent to which itsimplementation reflects the principles of justice and fiscal efficiency.Additionally, this study examines the relevance of this principle from anIslamic law perspective, particularly in relation to the concept ofrestorative justice and the state's role in realizing public welfare(maslahah). Using a normative juridical approach supported byempirical data from court decisions and interviews, this study finds thatthe ultimum remedium principle has not been consistently applied andtends to have no significant impact on state financial recovery. From anIslamic law standpoint, these findings reinforce the argument that asystem prioritizing the restoration of state rights (the rights of Baitul Mal)should take precedence over physical sanctions, in accordance with thespirit of justice oriented toward public benefit. As a novel contribution,this study proposes a restorative fiscal justice approach model thatpositions ultimum remedium as an active strategy for recovering losses,not merely as a principle of criminal limitation. These findings areexpected to strengthen the direction of economic criminal law reformtoward a system that is more proportional, efficient, and adaptive to stateneeds, while aligning with ethical and religious values.